Psychological Expert Witness Work in Indonesia - Arbiyah, Nurul; Sumampouw, Nathanael; Otgaar, Henry (Psychological Research on Urban Society, 2026)
In the current manuscript, we describe how forensic psychology evolved in Indonesia in research and practice settings and how psychologists work as expert witnesses in legal cases. We performed a literature search using SINTA (the portal of Indonesian accredited journals) to retrieve publications on "Forensic Psychology," "Legal Psychology," or "Law Psychology" to search for papers in Indonesian journals. We also explored relevant publications about forensic psychology in Indonesia in international journals using the Web of Science (WoS) database, which showed findings concerning the lack of publication. Additionally, a literature search using WoS resulted compared with other areas of psychology in Indonesia, forensic psychology research is lagging. Additionally, we conducted semi-structured interviews with five APSIFOR members, asking about their experiences as psychological expert witnesses in Indonesia, the policies governing their work, their challenges, and recommendations for improving their work. Lastly, we illustrate two significant cases that call for serious attention to the development of forensic psychology in Indonesia. We conclude by providing several recommendations for improving Indonesian psychological expert witness work, emphasizing the importance of clear guidelines and standards, establishing a forensic psychology education program, conducting additional research, and increasing the competence of psychological expert witnesses. Keywords: Forensic psychology, legal psychology, psychological expert witness, legal context, Indonesia